A comprehensive update on early gastric cancer: defining terms, etiology, and alarming risk factors. (4th March 2021) - Yang, Kuo; Lu, Lijie; Liu, Huayi; Wang, Xiujuan; Gao, Ying; Yang, Liu; Li, Yupeng; Su, Meiling; Jin, Ming; Khan, Samiullah
ABSTRACT: Introduction: Early gastric cancer (EGC) is a well-defined gastric malignancy that is limited to the mucosa or submucosa, irrespective of lymph node metastasis. At an early stage, gastric cancer often does not cause symptoms until it becomes advanced, and it is a heterogeneous disease and usually encountered in its late stages. Area covered: This comprehensive review will provide a novel insight into the evaluation of EGC epidemiology, defining terms, extensive etiology and risk factors, and timely diagnosis since prevention is an essential approach for controlling this cancer and reducing its morbidity and mortality. Expert opinion: The causative manner of EGC is complex and multifactorial. In recent years, researchers have made significant contributions to understanding the etiology and pathogenesis of EGC, and standardization in the evaluation of disease activity. Though the incidence of this cancer is steadily declining in some advanced societies owing to appropriate interventions, there remains a serious threat to health in developing nations. Early detection of resectable gastric cancer is crucial for better patient outcomes.